Modular One‐Step Three‐Component Synthesis of Tetrahydroisoquinolines Using a Catellani Strategy - Qian, Guangyin; Bai, Miao; Gao, Shijun; Chen, Han; Zhou, Siwei; Cheng, Hong‐Gang; Yan, Wei; Zhou, Qianghui (Angewandte Chemie International Edition, 2018)
Reported is a modular one‐step three‐component synthesis of tetrahydroisoquinolines using a Catellani strategy. This process exploits aziridines as the alkylating reagents, through palladium/norbornene cooperative catalysis, to enable a Catellani/Heck/aza‐Michael addition cascade. This mild, chemoselective, and scalable protocol has broad substrate scope (43 examples, up to 90 % yield). The most striking feature of this protocol is the excellent regioselectivity and diastereoselectivity observed for 2‐alkyl‐ and 2‐aryl‐substituted aziridines to access 1,3‐cis‐substituted and 1,4‐cis‐substituted tetrahydroisoquinolines, respectively. Moreover, this is a versatile process with high step and atom economy. A modular synthesis of tetrahydroisoquinolines was developed. Aziridines act as the alkylating reagents to enable a Catellani/Heck/aza‐Michael addition cascade by palladium/norbornene (NBE) cooperative catalysis. This mild, chemoselective, and scalable protocol is compatible with a wide range of readily available aryl iodides, aziridines, and olefins. Excellent regio‐ and diastereoselectivities are observed for 1,3‐cis‐substituted and 1,4‐cis‐substituted tetrahydroisoquinolines.